The Grammar of Multilingualism - Terje Lohndal (Frontiers Research Topics, 2016)
This volume investigates the nature of grammatical representations in speakers who master multiple languages. Since the early days of modern formal approaches to grammar, most work has been based on the language of monolingual humans. Less work has been conducted based on data from speakers who possess more than one language. Although important insights have been gained from a monolingual focus, there is every reason to believe that bi- and multilingual data can inform linguistic theory. A lot of ongoing work demonstrates that this is indeed the case, and the current volume contributes to this growing literature. Thus, the research topic addresses a number of questions relating to grammatical structures in multilingual speakers as well as the methodological issues that arise in the context of studying such speakers. A better understanding of the grammatical sides of multilingualism is crucial for understanding the human language capacity and in turn for offering better advice to the public concerning issues of language choice for multilingual children and adults, education, and language deficits in multilingual individuals.